Ego Depletion, Professional Skepticism, and Decision-making Quality in Forensic Auditors - Hani Shirowzhan; Hossien Fakhari (بررسی‌های حسابداری و حسابرسی)
Objective Judgment and decision-making are integral to any auditing activity and become more complex depending on the nature of the judgment and the subject of the decision. Therefore, identifying the factors that affect this process is essential. Among these factors, professional skepticism plays a significant role in the quality of judgment and decision-making. However, the impact of professional skepticism varies when the decision-maker experiences diminished self-control or ego depletion. This study is significant due to the diverse and economically consequential groups affected by accounting judgments and decision-making, and it helps justify why certain judgments and decisions are made. Consequently, the primary aim of this research is to examine the role of professional skepticism in shaping the quality of judgment and decision-making among forensic auditors and to explore the moderating effect of ego depletion on these processes. Methods The present research used a non-probability sampling method with available samples. Data were collected through standard questionnaire distribution and direct contact with 950 Iranian members of the official judiciary experts in accounting and auditing (members of the justice official expert and judicial authority), ultimately resulting in the receipt of 300 completed questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with SPSS and Smart PLS software. Results The research findings are practically useful for diverse groups and offer valuable insights to both the forensic auditing community and researchers. The results indicate that professional skepticism has a significant and positive effect on the quality of judgment and decision-making. In other words, an increase in professional skepticism improves the quality of judgment and decision-making among forensic auditors. Additionally, the findings suggest that most forensic auditors face issues related to overwork, which is the primary cause of ego depletion. Generally, ego depletion leads to a decrease in professional skepticism, ultimately resulting in a decline in the quality of judgment and decision-making among forensic auditors. Further findings showed that although there is a positive relationship between professional skepticism and the quality of judgment and decision-making, the effect of ego depletion is negative. However, this relationship varies at different levels. Conclusion The research findings can contribute to enhancing the productivity of forensic auditors concerning judgment and decision-making. In conclusion, these findings can be instrumental in diagnosing professional issues and elucidating factors that influence the quality of judgment and decision-making among forensic auditors. Additionally, third parties could be considered stakeholders in understanding why decision-makers make certain decisions and the consequences of those decisions.